Pengaruh Kepercayaan Diri dan Semangat Kewirausahaan terhadap Minat Menjadi Wirausaha - Sakinah Sakinah; Zuhrinal M. Nawawi (ManBiz: Journal of Management and Business, 2023)
Becoming an entrepreneur is one solution to overcome the problem of unemployment, because now people will not be satisfied with meeting their needs only relying on the results of being an employee. The increasing need, this affects the people themselves to be able to survive or not live their lives, and therefore becoming an entrepreneur is one of the solutions in addition to unemployment problems but also human survival. The purpose of this study was to obtain an overview of entrepreneurial interest and to test hypotheses regarding the effect of self-confidence and entrepreneurial spirit on interest in becoming an entrepreneur. The method used in this research is descriptive research. In accordance with the objectives to be achieved, this research uses the research method used is the survey method. The sampling in this study was from a population of 663 students of the economics faculty, level I, II, and III with a sample of 10% in each batch. The results of the analysis show that positive self-confidence towards interest in becoming an entrepreneur is partially and significantly with a linear regression coefficient of 0.342, entrepreneurial spirit has a positive effect on interest in becoming an entrepreneur partially and significantly with a regression coefficient of 0.447, and self-confidence and entrepreneurial spirit have a positive effect simultaneously. and significant to the interest in becoming an entrepreneur with the regression equation Y = 3.109 + 0.342X1 + 0.447X2. The results of the coefficient of determination show that changes in interest in becoming an entrepreneur can be influenced by changes in self-confidence and entrepreneurial spirit by 22.6%, the remaining 77.4% is influenced by other factors. Keywords: Entrepreneurship, Entrepreneurship, Linear Regression Coefficient